1991
DOI: 10.1002/pd.1970110506
|View full text |Cite
|
Sign up to set email alerts
|

Early amniocentesis at 11–14 weeks' gestation for the diagnosis of fetal chromosomal abnormality—a clinical evaluation

Abstract: Early amniocentesis between 11 and 14 weeks' gestation was offered to 110 women at risk of a chromosomally abnormal fetus due to maternal age. Four were found to be unsuitable for the procedure, and 106 early amniocenteses were performed. In 102 cases, clear amniotic fluid was obtained with a single tap. There were two dry taps and two bloodstained taps; sampling was repeated in three of these cases before 15 weeks. In the fourth case, placental biopsy was performed at 16 weeks. Thus, we were able to obtain a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 6 publications
(4 reference statements)
4
14
1
Order By: Relevance
“…These results compare favorably with pre viously published observational studies of EA where the estimated rates of procedure-relat ed fetal loss range from 3.3 to 6.6% [7][8][9][10][11][12], In a series of 1,800 EA procedures (at 10 weeks and 4 days to 13 weeks and 6 days) recently reported by Eibcn ct al. [13], the total fetal loss rate (to 24 weeks) was 1%, which is also not significantly different from the current study [1.8% to 24 weeks (95% Cl 0.3-3.4%)].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These results compare favorably with pre viously published observational studies of EA where the estimated rates of procedure-relat ed fetal loss range from 3.3 to 6.6% [7][8][9][10][11][12], In a series of 1,800 EA procedures (at 10 weeks and 4 days to 13 weeks and 6 days) recently reported by Eibcn ct al. [13], the total fetal loss rate (to 24 weeks) was 1%, which is also not significantly different from the current study [1.8% to 24 weeks (95% Cl 0.3-3.4%)].…”
Section: Discussionsupporting
confidence: 75%
“…In addition, recent findings concerning the asso ciation of CVS with limb reduction abnormal ities have placed the relative safety of CVS in question [4][5][6], Early amniocentesis (EA), performed be tween 11 and 14 weeks of gestation, is an alternative to both CVS and MA that appears to combine the safety of MA with earlier availability of results. While preliminary data suggest that the safety and accuracy of EA is similar to MA, none of the studies to date have had the power to adequately assess the risk of fetal loss, particularly between 11 and 12 weeks of gestation [7][8][9][10][11][12]. Nonetheless, EA is gradually gaining clinical acceptance in many centers in both North America and Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Other congenital malformations such as talipes and congenital dislocated hips have been reported at an increased incidence following amniocentesis. Hackett et al [10] identified four congenital abnormalities (imperfo rate anus, hemangioma of the tongue, two positional tal ipes) in 62 babies following EA at 11-14 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…2 Early ultrasound (12-14 weeks) is also a reliable option when performed at specialized centers. [3][4][5] Invasive testing, either using chorionic villus sampling from 11 weeks or amniocentesis from 15 weeks, [6][7][8] is also an option and allows definitive genetic diagnosis, but both techniques carry a small but significant miscarriage risk (B1%). 9 When used for determination, NIPD has a number of advantages over ultrasound and invasive testing.…”
Section: Introductionmentioning
confidence: 99%